2021
DOI: 10.1007/s00125-020-05341-y
|View full text |Cite
|
Sign up to set email alerts
|

Reducing intergenerational obesity and diabetes risk

Abstract: To address the intergenerational transmission of obesity and diabetes, strategies promoting the health of women of reproductive age appear to be urgently needed. In this narrative review, we summarise what has been learned from many prenatal clinical trials, discuss the emerging evidence from preconception clinical trials and highlight persistent gaps and critical future directions. Most trials tested prenatal interventions that resulted in a limited gestational weight gain of~1 kg and reduced gestational diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…This is not only biologically plausible but clinically relevant. Our results join the accumulating evidence that prepregnancy health is an important determinant of pregnancy health (37,50,51).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is not only biologically plausible but clinically relevant. Our results join the accumulating evidence that prepregnancy health is an important determinant of pregnancy health (37,50,51).…”
Section: Discussionsupporting
confidence: 86%
“…Ameliorating excess GWG is important in order to reduce APOs such as preeclampsia, gestational diabetes, and severe maternal morbidity that have consequences for perinatal and long‐term health outcomes (1‐4,36). In addition, weight gain is progressive and cumulative in women during the reproductive years, and GWG contributes to these patterns (37‐39). Our data suggest that attention to the preconception patterns of gain is important for pregnancy health and its lifelong contribution to risk for obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fetal AWT and long-term health of offspring remains unknown. With evidence to support increasing prevalence and disease severity of type 2 diabetes with each successive generation affected [46][47][48], there is question as to whether or not a thicker fetal subcutaneous fat layer might represent an early marker of future metabolic disease. Overall, fetuses in our study had thicker subcutaneous fat layers than described in other studies (8.2 mm at 35 to 36 weeks versus 5.4 mm at 35 to 39 weeks in the Higgins study) [25]: this difference may be related to the restriction of our study population to only those mothers with confirmed pregestational type 2 diabetes or it may be a consequence of a poorer underlying maternal metabolic environment of mothers in our cohort including higher rates of morbid obesity.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 15 This propensity for metabolic dysfunction that links mother and child may be the consequence of multiple elements including (i) shared genetic factors, (ii) the home environment and associated lifestyle, and (iii) fetal exposure to the altered intrauterine environment of the GDM pregnancy, which potentially may program adverse developmental pathways as per the Developmental Origins of Health and Disease (DOHaD) paradigm. 16 , 17 , 18 , 19 , 20 Moreover, evidence to date suggests that current antepartum treatment of GDM does not reduce these future risks in the offspring 21 , 22 and it remains uncertain whether non-insulin pharmacologic therapy for GDM (such as glyburide or metformin) could even have deleterious effects on the offspring that might emerge during childhood. 23 …”
Section: Future Health Implications Of Gdm After Pregnancymentioning
confidence: 99%